DAMPAK LITERASI KEUANGAN DIGITAL TERHADAP PERILAKU KEUANGAN MAHASISWA UNIVERSITAS BINAWAN - Sahamony, Nur Fitriyani (POLITEKNIK LP3I JAKARTA, 2023)
The purpose of this study was to find out whether there s an nfluence between financial literacy on the financial behavior of Binawan Uiniversity students. The research method used n this research s descriptive analysis with a quantitative approach. The sample used was 98 and were active students at Binawan Uiniversity. The results of the study show that there s an nfluence between financial literacy on the financial behavior of Binawan Uiniversity students. The results of the regression test show that the coefficient of determination (R2) s 0.973 or 97.3%. This value ndicates that 97.3% of financial behavior s nfluenced by financial literacy, while the remaiining 2.7% s nfluenced by other variables not examined n this study.Key words: Financial Literacy, Financial Behavior, Student Finance